Sekundäre Märkte? Zum Wiener und Salzburger Gebrauchtwarenhandel im 17. und 18. Jahrhundert - Stöger, Georg (2011)
Few historians have followed the entire "life-cycle" of a product; especially "secondary" forms of use, transfer and alteration - for example repair works or the trade in used goods - often have been neglected.